Metabolic alterations in pea leaves during arbuscular mycorrhiza development - Shtark,Oksana Y.; Puzanskiy,Roman K.; Avdeeva,Galina S.; Yurkov,Andrey P.; Smolikova,Galina N.; Yemelyanov,Vladislav V.; Kliukova,Marina S.; Shavarda,Alexey L.; Kirpichnikova,Anastasiia A.; Zhernakov,Aleksandr I.; Afonin,Alexey M.; Tikhonovich,Igor A.; et al. (PeerJ, 2019)
Arbuscular mycorrhiza (AM) is known to be a mutually beneficial plant-fungal symbiosis; however, the effect of mycorrhization is heavily dependent on multiple biotic and abiotic factors. Therefore, for the proper employment of such plant-fungal symbiotic systems in agriculture, a detailed understanding of the molecular basis of the plant developmental response to mycorrhization is needed. The aim of this work was to uncover the physiological and metabolic alterations in pea (Pisum sativum L.) leaves associated with mycorrhization at key plant developmental stages. Plants of pea cv. Finale were grown in constant environmental conditions under phosphate deficiency. The plants were analyzed at six distinct time points, which corresponded to certain developmental stages of the pea: I: 7 days post inoculation (DPI) when the second leaf is fully unfolded with one pair of leaflets and a simple tendril; II: 21 DPI at first leaf with two pairs of leaflets and a complex tendril; III: 32 DPI when the floral bud is enclosed; IV: 42 DPI at the first open flower; V: 56 DPI when the pod is filled with green seeds; and VI: 90–110 DPI at the dry harvest stage. Inoculation with Rhizophagus irregularis had no effect on the fresh or dry shoot weight, the leaf photochemical activity, accumulation of chlorophyll a, b or carotenoids. However, at stage III (corresponding to the most active phase of mycorrhiza development), the number of internodes between cotyledons and the youngest completely developed leaf was lower in the inoculated plants than in those without inoculation. Moreover, inoculation extended the vegetation period of the host plants, and resulted in increase of the average dry weight per seed at stage VI. The leaf metabolome, as analyzed with GC-MS, included about three hundred distinct metabolites and showed a strong correlation with plant age, and, to a lesser extent, was influenced by mycorrhization. Metabolic shifts influenced the levels of sugars, amino acids and other intermediates of nitrogen and phosphorus metabolism. The use of unsupervised dimension reduction methods showed that (i) at stage II, the metabolite spectra of inoculated plants were similar to those of the control, and (ii) at stages IV and V, the leaf metabolic profiles of inoculated plants shifted towards the profiles of the control plants at earlier developmental stages. At stage IV the inoculated plants exhibited a higher level of metabolism of nitrogen, organic acids, and lipophilic compounds in comparison to control plants. Thus, mycorrhization led to the retardation of plant development, which was also associated with higher seed biomass accumulation in plants with an extended vegetation period. The symbiotic crosstalk between host plant and AM fungi leads to alterations in several biochemical pathways the details of which need to be elucidated in further studies.
Keywords: Pisum sativum; Arbuscular mycorrhiza; Plant growth and physiological state; Leaf; Metabolic profile